Oral cavity and extra-oral plasmablastic lymphomas in AIDS patients: Report of five cases and review of the literature - Corti, Marcelo (2011)
Plasmablastic lymphoma (PBL) is a distinct disease entity of the diffuse large B-cell lymphoma, which often occurs in HIV-positive patients. The immunophenotype of this lymphoid neoplasm is characterized by the presence of plasma cell-associated markers VS38c and CD138 antigens and the absence of B-cell markers such as CD20 and CD45. The most frequent site of involvement is the oral cavity and the jaw, while several reports describe the development of PBL in extra-oral sites including the lymph nodes, the anal canal, the soft tissue, the skin and the gastrointestinal tract as less frequent. Epstein Barr virus is often associated with PBL pathogenesis and the neoplastic cells contain this virus genome. Here we review the epidemiological, clinical, immunological, histopathological and virological characteristics and their prognosis and outcome in a series of five patients with diagnoses of HIV/AIDS and PBL.